2020
DOI: 10.1002/jcla.23488
|View full text |Cite
|
Sign up to set email alerts
|

The value of circulating long non‐coding RNA maternally expressed gene 3 as a predictor of higher acute respiratory distress syndrome risk and 28‐day mortality in sepsis patients

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…In this study, we found that more nonsurvivors were male, older and had MODS than survivors, which has been validated in various studies 14,15 …”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In this study, we found that more nonsurvivors were male, older and had MODS than survivors, which has been validated in various studies 14,15 …”
Section: Discussionsupporting
confidence: 65%
“…In this study, we found that more nonsurvivors were male, older and had MODS than survivors, which has been validated in various studies. 14,15 The multivariable logistic analysis also suggested that lower albumin and CRP were independent risk factors for a 28-day poor prognosis of ARDSp based on the 10 years of clinical data, especially CRP, which seemed to be a paradox.…”
Section: Discussionmentioning
confidence: 97%
“…In another study, Gui et al concluded that lncRNA Antisense non-coding RNA in the INK4 locus (ANRIL)/miR-125a axis was upregulated in sepsis patients (107), which suggest that ANRIL could work as another potential biomarker for sepsis risk and severity. Several studies have suggested that lncRNA maternally expressed gene 3 (MEG3) might serve as a valuable indicator for the progression of sepsis, providing new strategy against acute respiratory distress syndrome in sepsis (108,109).…”
Section: Lncrnas In Diagnosis and Prognosis Of Sepsismentioning
confidence: 99%
“…As a major protein related to innate immune and inflammatory responses, TLR3 is known to cause cardiac dysfunction and other organ damage during sepsis ( 74 , 75 ). Low expression of lnc-MEG3 might also serve as a potential biomarker for the development, progression, and prognosis prediction of sepsis ( 76 78 ). Furthermore, overexpression of MEG3 prevented LPS-induced macrophage apoptosis and secretion of inflammatory factors by inhibiting activation of the NF-κB signaling pathway ( 77 ).…”
Section: Lncrna Involved In Sicd Among Various Cell Typesmentioning
confidence: 99%